Evaluating the usefulness of continuous leaf turgor pressure measurements for the assessment of Persimmon tree water status - Martínez-Gimeno, María A.; Castiella, M.; Rueger, S.; Intrigliolo, Diego S.; Ballester, Carlos (2018)
Continuous plant water status monitoring is crucial in order to improve irrigation management. The noninvasive Yara ZIM-probe was assessed for detecting plant water stress in Persimmon trees (Diospyros kaki L.f.). The probe measures the pressure transfer function (P (p)) through a patch of an intact leaf, which is inversely correlated with the turgor pressure. This technology was evaluated in two parallel experiments involving either distinct watering regimes or rootstocks with different drought tolerance [Diospyros lotus (L) and Diospyros virginiana (V)]. Concomitant measurements of midday stem water potential (I (stem)) and trunk diameter variations were taken throughout the experiments. P (p) was highly correlated with I (stem). Persimmon leaves exhibited the inversed P (p) curve phenomena under water stress, which enabled the association of a particular range of I (stem) to each of the three leaf turgor states defined. Persimmon trees with no sign of initial or total inversion ensured I (stem) above -0.8 MPa, values considered of a well-watered Persimmon tree. Yara ZIM-probe readings as well as I (stem) and trunk diameter variation measurements pointed L as a more sensitive rootstock to drought than V. In conclusion, results showed that the Yara ZIM-probe can be used to continuously monitor water status in Persimmon trees although further research would be needed to ensure their feasibility for scheduling irrigation.